Fundamental ekonomi dan krisis ekonomi Indonesia - Sahabudin Sidiq (Economic Journal of Emerging Markets, 1999)
Since July 1997, Asia-Pasific countries have been fighting to handle monetary crisis they face. Among those countries, few countries are able to handlle the crisis relatively quickly while Indonesia seems to have a difficulty in handling the crisis. As this article extends, it happens because the fundamental of the Indonesian economy is less weak rather than those countries.